Peningkatan Hasil Belajar Alqur’an Hadist Melalui Metode Tahsin (Membaca) Pada Siswa Kelas XI MAS Jam’iyah Mahmudiyah Tanjung Pura - Erwin Syahputra (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
This research aims to improve the ability to memorize the Qur'an of grade VII MTsS Jam'iyah Mahmudiyah students through the Role Playing method. The research uses a classroom action approach (Classroom Action Research) with two cycles, each cycle includes the stages of planning, implementation, observation, and reflection. In the pre-cycle, only 31% of students achieved completeness with KKM 75. After the application of the Role Playing method in cycle I, the completeness increased to 71%. In cycle II, the percentage of completion increased significantly to 91%. These results show that the Role Playing method is effective in improving students' ability to memorize the Qur'an, increase their active participation, and motivation to learn.